Development of specific monoclonal antibodies for the detection of natural chicken tumor necrosis factor-alpha. Issue 12 (December 2022) - Yang, Yi; Meng, Yining; Chen, Lina; Dong, Maoli; Zhang, Huining; Wu, Ji; Hao, Xiaoli; He, Shuangjiang; Tian, Yunfei; Gong, Zaicheng; Shang, Shaobin
Abstract: Tumor necrosis factor alpha (TNF-α) is an important proinflammatory cytokine and the only known cytokine that can directly kill tumor cells. Unlike mammalian counterparts, chicken TNF-α (chTNF-α) gene has not been identified until very recently due to its high GC content (∼70%) and long GC fragments. The biological functions of this newly-identified cytokine and its detection methods remain to be further investigated. In this study, the extracellular domain of chTNF-α was cloned into prokaryotic vector after codon optimization and recombinant chTNF-α protein was expressed. Subsequently, using recombinant chTNF-ɑ as immunogen, rabbit polyclonal antibody (pAb) and eight clones of mouse anti-chTNF-ɑ monoclonal antibodies (mAbs) were produced, respectively. Both the pAb and mAbs specifically recognized recombinant chTNF-ɑ expressed in E.coli and transfected COS-7 cells. Further mapping the antigenic region showed that all the mAbs recognized a region of amino acid residues 195–285 of chTNF-ɑ. Furthermore, an antigen-capture enzyme-linked immunosorbent assay for the detection of chTNF-ɑ was established using one mAb and the pAb. This assay showed no cross-reactivity with irrelevant Trx-fused antigens and could detect natural chTNF-ɑ expressed by mitogen-activated chicken splenocytes in a dose-dependent manner, with a detection limit of 1 ng/mL. Collectively, our results indicated that the mAbs and pAb against chTNF-α are specific and could be used for the study of the biological functions of chTNF-ɑ and the detection of chTNF-ɑ. Abstract : chTNF-α; Monoclonal antibody; Polyclonal antibody; Epitope mapping; Antigen-capture ELISA.